Decorating old house interiors : American classics, 1650-1960 - Schwin, Lawrence (New York : Sterling, 1994)
Colorful illustrations, photographs, and text present detailed views of the major decorative periods from 1650 to 1960.
-- The Earliest Colonials (1650-1700) -- Tidewater Manors (1700-1725) -- The Georgians (1730-1760) -- Fashionable, Plain, and Neat (1760-1775) -- The Philadelphia Rococo (c.1775) -- Farmers' Formal (1800-1840) -- Designs for a Young Republic (1790-1820) -- The Nation's Architect (c. 1810) -- Pineapples, Starbursts, and Swags (1810-1840) -- Outdoors/Indoors (1800-1840) -- Home and Hearth (1800-1840) -- The Greek Revival (1830-1845) -- The Gothic Revival (1835-1850) -- Rococo Meets Renaissance (1860-1870) -- The Renaissance Revival (1870-1880) -- The Exotic Craze (1875-1895) -- Queen Anne in America (1880--1890) -- The First Colonial Revival (1885-1900) -- Bay Area Rustic/Classical (1895-1915) -- Design Advice for the Elite (1900-1920) -- Home Sweet Home (1895-1910) -- Porches, Piazzas, and Sunrooms (c1875-1930) -- The Craftsman Era (c. 1905-1920) -- The Spanish Revivals (1910-1930) -- Bankers' Tudor (c. 1910-1930) -- The Decade of Dichotomies (c. 1930-1940) -- The International Style in America (c. 1936-1955) -- The Second Colonial Revival (1925-1950) -- The Baby Boomer Era (1945-1960) -- Working It Out for Yourself.
"A Sterling/Main Street book."
Includes bibliographical references (pages 153-155) and index.
Keywords: Interior decoration -- United States -- Themes, motives